2017
DOI: 10.14715/cmb/2017.63.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Organic chromium modifies the expression of orexin and glucose transporters of ovarian in heat-stressed laying hens

Abstract: In this study, the effect of the supplemental organic chromium (Cr) forms on the expression of ovarian orexin(hypocretin), glucose transporters (GLUTs), heat shock proteins (HSPs) andnuclear factor-kappaB (NF-κB)were investigated in laying hens (HS). Laying hens (n=1800; 16-wk-old; Lohmann LSL-Lite) were allocated to 6 random groups according to a 2 × 3 factorial trial scheme with two different environmental temperatures [Thermoneutral (TN groups; at either 22±2 °C 24 h/d)  and heat stress (HS groups; at 34±2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition to physiological implications, the impact of nutrition on the orexin system has limited investigation. A recent study has shown that dietary chromium increased orexin and GLUT expression levels and reduced levels of NF-κB and HSPs in the ovaries of heat-stressed laying hens, indicating nutritional interventions capable of modulating the orexin and inflammatory systems [ 88 ]. Further research into the impacts of nutrition on the orexin system within the peripheral tissues of chickens is warranted, and could provide insight into the mechanisms of improved stress response and energy homeostasis.…”
Section: Peripheral Role Of Orexinmentioning
confidence: 99%
“…In addition to physiological implications, the impact of nutrition on the orexin system has limited investigation. A recent study has shown that dietary chromium increased orexin and GLUT expression levels and reduced levels of NF-κB and HSPs in the ovaries of heat-stressed laying hens, indicating nutritional interventions capable of modulating the orexin and inflammatory systems [ 88 ]. Further research into the impacts of nutrition on the orexin system within the peripheral tissues of chickens is warranted, and could provide insight into the mechanisms of improved stress response and energy homeostasis.…”
Section: Peripheral Role Of Orexinmentioning
confidence: 99%
“…Zinc is one of the most crucial trace minerals for nutrition and a crucial part of many biological processes [10]. Zinc has a vital role in metalloenzymes and has both structural and catalytic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent chromium could improve insulin sensitivity and glucose utilization in animals and humans who suffer from metabolic diseases such as type 2 diabetes and obesity [ 16 , 17 ]. In several studies, the glucose transporters in heat-stressed poultry could be improved by supplementing their diets with organic chromium, which is conducive to maintaining glucose homeostasis [ 18 , 19 , 20 ]. However, there has been no report about the influence of chromium on glucose homeostasis involved in the microflora in heat-stressed chickens.…”
Section: Introductionmentioning
confidence: 99%